Academic library opportunity: examining the research data management challenges facing Malaysian information science researchers / Wahidah Mohd Zain ... [e at.] - Mohd Zain, Wahidah; Ahmad, Zahril Shahida; Paula, Lackie; Kamarudin, Norkamarizal; Nordin, Siti Khairiyah (Faculty of Information Management, 2023)
Research Data Management (RDM) is pivotal in fostering scientific communication, ensuring long-term data storage, and facilitating research verification. Despite its significance, there is a dearth of empirical studies examining RDM behaviors among researchers in Malaysia. This study fills this research gap by conducting a comprehensive investigation into the state of RDM in Malaysian academic libraries, with a particular focus on the initiatives of Universiti Teknologi MARA. Utilizing a mixed-methods approach, researchers' attitudes, practices, and challenges concerning RDM were explored. Preliminary findings suggest a fragmented approach to RDM, emphasizing the need for standardized practices and increased institutional support. The research underscores the crucial role that academic libraries can play in this context. Libraries are positioned not only as repositories but also as hubs for RDM knowledge dissemination, offering training and support to researchers. The study also delves into potential future directions for RDM in Malaysia, highlighting opportunities for academic libraries to further embed themselves in the research ecosystem. As RDM becomes increasingly integral in the global research landscape, this study serves as a timely examination of Malaysia's current stance and the steps it can take to ensure robust and effective RDM practices.